2019
DOI: 10.1371/journal.pone.0218622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter irrigation on soil salinity and jujube growth in arid regions

Abstract: The considerably high evapotranspiration and the low leaching fraction of the soil in arid regions are likely the primary causes of the enhanced soil salinity in such regions. Winter irrigation has proven to be very effective for promoting the leaching of salts from the rooting-zone. In this study, we investigated the effects of different irrigation methods (flood irrigation and drip irrigation) and winter irrigation quotas (450, 1350, 2250, 3150, 4050, and 4950 m 3 /hm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The most important causes of soil salinization are (1) the use of unsuitable irrigation water containing high salt concertation, (2) a high rate of soil transpiration, especially in the semi-arid and arid areas of the world, and (3) soil physicochemical and biological properties (Munns & Gilliham 2015;Zeng et al 2016). The accumulation of salt in the soil negatively affects plant growth and physiology by (1) increasing soil and plant osmotic potential, and subsequent decrease of water efficiency for plant use and (2) the toxic effects of ions such as sodium (Naþ) and chloride (Cl-) (Upadhyay & Singh 2015;Liu et al 2019).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The most important causes of soil salinization are (1) the use of unsuitable irrigation water containing high salt concertation, (2) a high rate of soil transpiration, especially in the semi-arid and arid areas of the world, and (3) soil physicochemical and biological properties (Munns & Gilliham 2015;Zeng et al 2016). The accumulation of salt in the soil negatively affects plant growth and physiology by (1) increasing soil and plant osmotic potential, and subsequent decrease of water efficiency for plant use and (2) the toxic effects of ions such as sodium (Naþ) and chloride (Cl-) (Upadhyay & Singh 2015;Liu et al 2019).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Yang et al [17] demonstrated that, as the winter irrigation rate increased, the soil salt leaching effect was enhanced, but irrigation water-use efficiency was reduced, with the optimal winter irrigation rates on cotton fields in southern Xinjiang being 1800-3600 m 3 •hm −2 . Liu et al [18] applied winter irrigation to jujube (Ziziphus jujube) plantations in southern Xinjiang and reported that drip irrigation in winter at a rate of 3150 m 3 •hm −2 could significantly increase soil water content and salt leaching, increase the survival rate of the jujube trees the following year, and promote their growth and development. The above studies showed that winter irrigation can increase soil water storage, inhibit soil temperature change, reduce soil surface salt content, promote soil microbial activities, indirectly change soil physical and chemical properties, and further affect crop growth in the next year.…”
Section: Introductionmentioning
confidence: 99%
“…The salt loading rates through irrigation are proportional to amount of water applied and their chemistry. Flood irrigation is widely used along the Rio Grande valley and other regions where fields inundate with water without any infrastructure 65 , 66 . The evaporative water loss during the irrigation season is problematic for freshwater-limited drylands.…”
Section: Resultsmentioning
confidence: 99%